(untitled) (American Journal of Islam and Society, 2002)
DHAOUADI: Based on my own observations and impressions, one talks more about sociology as a discipline having a crisis, than about psychology or political science. How do you respond to that? SMELSER: I heard this kind of talk among sociologists. Among the questions raised in their frequent conversations are: What is the field about? What are the boundaries about? Is it (sociology) fragmented? Is it practiced ... etc? In that disciplinary sense, every field in the social sciences has a problem to some degree. Economics, even has a problem about the con - flict between neoclassical economics and the various branches of this discipline, which internally , has become even more complex. They don’t beat their breast quite as much about this as sociologists, but if you talk to anybody in the field they will say: "Well, we have no unity, we have no consensus; it’s splitting up into too many specializations." We find the same kind of talk in sociology. Realistically, I think that sociology can probably be best compared with political science, in the sense that it is solidly established in the university system, so its organization is solid and its professional association is solid. Despite the conflict I mentioned earlier, it is recognized in the agencies that give money to the field, it’s recognized by publishers as being a field, and no one seems to be deserting it ...